IS GLYCEMIC CONTROL IN PATIENTS WITH TYPE-2 DIABETES IN RAWALPINDI IMPROVING? - Khan, Dilshad Ahmed; Saeed, Mariam; Khan, Farooq Ahmad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Glycaemic control is critical for managing diabetes and related complications. Considering high prevalence of Diabetes in Pakistan, our study aimed to assess the status of glycaemic control in Type-II Diabetics by measurement of HbA1c from 2005-2007 at Rawalpindi. We also evaluated changes in its trends in relation with sex and age. Methods: It was a retrospective analysis of data from Clinical Pathology Laboratory, Army Medical College, Rawalpindi during 2005-2007. A total of 2875 patients, aged 24-70 years, taking oral hypoglycaemic agents, were included. HbA1c was measured by using Human kit. International Diabetes Federation guidelines, ‰¤6.5%, 6.6%-8.4% and ‰¥8.5% were used to classify patients into good, fair and poor control categories. Results: The number of patients (n=2875) tested for HbA1c increased from 904,974 to 997 during 2005-2007. The patients had an age of 48±13 years and comprised of 54% males and 46% females. Improvement in patient's glycaemic control among the three categories during 2005 to 2007 was as follows: good (41% vs 47%), fair (38% vs 40%) and poor (21% vs 13%) respectively. The average HbA1c values improved from 7.25 % in 2005 to 6.69% in 2007 (p<0.05). Overall, males (45%) and youngest age group (53%) patients had good diabetic control. Conclusion: Glycaemic control improved in diabetic patients from 41% to 47% during 2005-2007 at Rawalpindi. Males, especially the youngest patients comprised majority of good control population. For effective disease management and optimal HbA1c values, a combined effort by the patient and physician is required. Keywords: Diabetes, Glycaemic Control, HbA1c, IDF guidelines, Pakistani population